American businesses in China : balancing culture and communication - Street, Nancy Lynch; Matelski, Marilyn J., 1950- (Jefferson, N.C. : McFarland & Co., 2008)
"This revised edition provides readers with a close understanding of the breathtaking technological and cultural evolution of 21st century China. The authors argue that after some 25 years of overt economic globalization, the Chinese have emerged as quite successful in their economic relationships with the West"--Provided by publisher.
Includes bibliographical references (p. 329-346) and index.
Keywords: Corporations, American -- China; Corporate culture -- China; China -- Economic conditions -- 2000-; National characteristics, Chinese